Over a million students use our free study notes to help them with their homework
Area of ABCD = (2x+5)(x+2) = 2x2 +9x +10Area of EFGH = (x+3)(x) = x2 + 3xTotal Area = 5 = ABCD - EFGH = 2x2 +9x +10 - x2 - 3x 5 = x2 + 6x +10 0 = xAnswered by Arad S. • Maths tutor2563 Views
First check if a, b and c all have a common factor.For example, if we have 3x²+6x+3=0, we can divide both sides by 3 and get x²+2x+1=0, which is easier to solve.If a,b and c do not all have a common facto...
Simultaneous equations have at least two unknowns that must have the same value in each equation. This means the value of x and y in both equations must...
Start again by drawing the graph and then the translated graphExplain what is meant by a translation ( a movement of the graph )Use a table of values to show how we can change the function to allow for di...
An increase by 20% is the same as multiplying by 1.2Therefore, 35 x 1.2 = 42
←
463
464
465
466
467
→
Internet Safety
Payment Security
Cyber
Essentials